Social Enterprise Among University-Based Centers in US Schools of Social Work. Issue 1 (2nd January 2016) - Sliva, Shannon M.; Hoefer, Richard
Abstract : Globally, social enterprise is used increasingly by nonprofit organizations to create new funding streams in the face of dwindling public funds. In light of evidence that institutions of higher education are making similar adaptations, this study explores the extent to which academic centers in US schools of social work are using social enterprise strategies to fund mission efforts. Interviews with the directors of 16 social work research centers in 14 states reveal incentives and barriers that exist at multiple levels and considerably impact the potential viability of social enterprise in the social work academic setting. Implications for institutions of higher education and social work scholars are discussed.